Issues in Energy Optimization of Reinforcement Learning Based Routing Algorithm Applied to Ad-hoc Networks (Informatica, 2025)
Issues in Energy Optimization of Reinforcement Learning Based Routing Algorithm Applied to Ad-hoc Networks